A new genus and eight new species of Phyllocoptini (Acari: Eriophyidae: Phyllocoptinae) from China - Xue, Xiao-Feng; Hong, Xiao-Yue (Zootaxa, 2005)
A new genus and eight new species of eriophyid mites from China are described: Paraepitrimerus sanguisorbae n. gen. and n. sp. on Sanguisorba officinalis L.; Paraepitrimerus paeoniae n. sp. on Paeonia lactiflora Pall.; Paraepitrimerus erigeronsis n. sp. on Erigeron annuus (L.) Pers.; Epitrimerus sabinae n. sp. on Sabina chinensis (L.) and Sabina chinensis cv. Kaizuca; Epitrimerus gnaphali n. sp. on Gnaphalium luteo-album L.; Epitrimerus amygdali n. sp. on Amygdalus triloba (Lindl.) Ricker.; Phyllocoptruta sanguisorbae n. sp. on Sanguisorba officinalis L. and Phyllocoptes fabris n. sp. on Abies fabri (Masters) Craib. All species described here are vagrants on leaves.